Discourse and conflict: examining the occurence, management and resolution of politically motivated conflict in Zimbabwe between 1980 and 1990 - Sibanda, Thabani (My University, 2012)
The study examined discursive practices followed during the conflict that took place in Zimbabwe between 1980 and 1990. Understanding conflict within discourse theory was the focal point of the study. Using discourse theory and analysis as tools to understand the conflict, the researcher sought to reveal how discourse was used in the conflict. The study sought to understand how discourse was intertwined with actions of the Zimbabwean government in carrying out massacres, detentions and disappearances of civilians. The aim of this study was to examine if there were particular ways in which discourse was harnessed or deployed to engender, provoke, justify, mitigate, legitimise and manage conflict by specifically examining discourses on the occurrence of the Matebeleland and the parts of Midlands Massacres in Zimbabwe between 1980 and 1990. The research questions for the study were as follows: 1.2.2.1 What issues are uncovered in the testimonies from the Consultative Group Process to assist in the construction of the research process? 1.2.2.2 How is discourse harnessed to legitimate conflict and protect the hegemonic space? 1.2.2.3 How is discourse used in the justification of the conflict? 1.2.2.4 In what ways is moral exclusion and othering demonstrated in the text? 1.2.2.5 What are some of the discursive practices followed in the exclusion of the target group? 1.2.2.6 In what ways is conflict managed and resolved? The philosophical underpinnings to the research are that; 1) Conflict is endemic in society though not all conflicts are harmful. 2) Negative conflict is associated with physical violence while positive conflict exists within the normative of social tensions and discomfort. 3) Violent The philosophical underpinnings to the research are that; 1) Conflict is endemic in conflict at macro levels typically arises from repressive systems such as authoritarian leadership, exclusions of the minority from governmental participation, socio-economic deprivation, poor institutional capacity to deal with conflict and lack of political will at State level to manage conflict. 4) What has remained constant in defining conflict across generations is that the conflicting parties ‘tend to have different needs, pursue antagonistic interests, values and access to power and resources is uneven’. The study was a qualitative discursive design, permitting the researcher to explore in depth the information obtained. It sought explanations about issues and commentary of human experience, with the acknowledgement that such experience is mediated. The study is important because the conflict in Zimbabwe still persists. Therefore if we understand how discourses were used in the 1980 to 1990 conflict, we have a better chance of understanding the current context. Using this design permits the construction of meanings to enable one to understand power relations– ideological and institutional arrangements that perpetuate political conflicts. The study analysed data from a Consultative Group Process (explained below) and secondary information from selected documents and newspaper publications from the State owned newspapers, namely The Chronicle and The Herald that were implicated in inciting conflict which led to the detentions and death of many people in Matebeleland and parts of the Midlands in Zimbabwe between 1980 and 1990. The study reviewed the literature on discourse and analysis from a critical perspective. In addition, archival research on key articles was undertaken to provide useful background to the study. During the data collection, the study used a Consultative Group Process. This group’s role was intended to create a framework of data collection that included follow-up of known experiences, stories from the community and documents that informed the researcher of the forms of discourses that developed out of the conflict in Zimbabwe. A consultative group of ten people with in-depth knowledge of Zimbabwe and had lived in the country at the time of the conflict, was recruited for the study. The members of the group were purposively selected based on their experiences of the conflict, using a snowball sampling technique. These people were consulted in the formulation of the research, discussion guide, identification of readings to be analysed, analysis of discourses and commentary on the study. The analysis of the findings both from the group discussions and newspaper reports showed that there was complicity by the State-owned media in the atrocities committed by the government against the civilian populations in Matebeleland and parts of the Midlands. The key social groups alienated and targeted by the state were the Ndebele and ideology (or belief systems), and persistent articulations that conveyed exclusion, domination and elimination of resistance. The most common discourses were drawn from the group discussions and newspaper ZAPU members. Anyone else associated with these groups were also likely to be termed articles. The media discourses were aligned to the government’s pursuit of hegemony. This study outlines the role of psychologists in using discursive psychological approaches. The study argues that psychologists could play a significant role in gathering evidence, through discourse analysis, that is, examining how language is used to influence people’s thought Ndebele and ‘dissident’ or ‘bandit.’ The discursive practices were characterised by processes during the creation of conflict and violence. The elimination of the opposition gave opportunity to ZANU PF to entrench power. Various strategies which included reification, legitimating, dissimilation and fragmentation were used to disintegrate the opposition. PF ZAPU was linked to dissidents in many newspaper articles. During the establishment of the unity process in 987, PF ZAPU would be blamed should there by stalling of the discussions, as evidenced in some articles.
Ph.D. -- University of the Witwatersrand, Faculty of Humanties, 2011.